2015
DOI: 10.5194/hess-19-2821-2015
|View full text |Cite
|
Sign up to set email alerts
|

Including the dynamic relationship between climatic variables and leaf area index in a hydrological model to improve streamflow prediction under a changing climate

Abstract: Abstract. Anthropogenic climate change is projected to enrich the atmosphere with carbon dioxide, change vegetation dynamics and influence the availability of water at the catchment scale. This study combines a nonlinear model for estimating changes in leaf area index (LAI) due to climatic fluctuations with the variable infiltration capacity (VIC) hydrological model to improve catchment streamflow prediction under a changing climate. The combined model was applied to 13 gauged sub-catchments with different lan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…This finding is similar to that of a study by Breda et al [80], where E T is not correlated with DBH, but more related to LAI. Furthermore, Granier et al [81] found that a reduction in LAI was associated with a decrease in E T in open stands as a result of the reduction of the transpiring canopy surface, and that it was not associated with a decrease of total E. Other studies have also determined that changes in LAI could alter E partitioning in E G and E T by regulating the ratio between area covered by the canopy and stands opening [82][83][84][85].…”
Section: E T /E At the Seasonal Scalementioning
confidence: 99%
“…This finding is similar to that of a study by Breda et al [80], where E T is not correlated with DBH, but more related to LAI. Furthermore, Granier et al [81] found that a reduction in LAI was associated with a decrease in E T in open stands as a result of the reduction of the transpiring canopy surface, and that it was not associated with a decrease of total E. Other studies have also determined that changes in LAI could alter E partitioning in E G and E T by regulating the ratio between area covered by the canopy and stands opening [82][83][84][85].…”
Section: E T /E At the Seasonal Scalementioning
confidence: 99%
“…Several studies have documented that VIC soil moisture simulation is strongly sensitive to how vegetation cover [Ford and Quiring, 2013;Tesemma et al, 2015] and soil properties [Billah and Goodall, 2012;Ford and Quiring, 2013;Lee et al, 2011;Liang et al, 1996;Lohmann et al, 1998b] are…”
Section: Discussionmentioning
confidence: 99%
“…Thus, areas of heavily managed forests in the lowlands tend to have lower LAIs and ET SUM to P ratios than less disturbed areas at higher elevations. Note that relatively few river basin scale hydrologic simulation models account for management or climate‐related variation in LAI (e.g., Tesemma, Wei, Peel, & Western, ). Here, we estimated LAI indirectly by way of stand age, but both satellite and airborne remote sensing have potential for mapping LAI (Livneh et al, ) and could be used to specify initial conditions for basin‐scale hydrology models.…”
Section: Discussionmentioning
confidence: 99%